Health Financing in Ghana - Schieber, George; Cashin, Cheryl; Saleh, Karima; Lavado, Rouselle (Washington, DC: World Bank, 2012)
The report is divided into five chapters. This chapter provides background on demographic and epidemiological trends, the configuration of Ghana's health system, and health financing functions and health systems goals. It also describes Ghana's health financing system. Chapter two assesses the performance of Ghana's health system with respect to these goals through international comparisons of health outcomes, inputs, spending, and financial protection as well as time series comparisons of trends in other countries in Africa. Chapter three identifies the strengths and weaknesses of Ghana's health system, which determine Ghana's health reform baseline. Chapter four analyzes the sustainability of the National Health Insurance Scheme, or NHIS in the context of Ghana's future fiscal space, based on Ghana's new standing as a lower-middle-income country. Chapter five analyzes major structural and operational reform options that will help ensure the long-term efficacy and sustainability of the NHIS.